“Turismo de trasplantes” e (in)securitización de las movilidades por salud - Basualdo, Lourdes (El Colegio de México, 2023)
This article seeks to analyze the process of in(in)securitization of health mobilities defined as "transplant tourism.” It focusses on the emergence and circulation of the "transplant tourism" category, as well as certain political uses of the concept in transplant and migration regulations in Argentina. It argues that "transplant tourism" was constructed as a problem of (in)security associated with the dangers and threats posed by certain types of mobilities to the "national order" of transplants and “international security,” because of its association with illicit forms of organ extraction and commercialization. The article uses a qualitative methodology combining the analysis of documentary sources with interviews with government officials in the Argentinean context.